The basal free fatty acid concentration in human saliva is related to salivary lipolytic activity - Neyraud, Eric; Cabaret, Stéphanie; Brignot, Hélène; Chabanet, Claire; Labouré, Hélène; Guichard, Elisabeth; Berdeaux, Olivier (Scientific reports, 2017)
Fat perception during eating is a complex sensation that involves various sensory modalities, such as texture, aroma and taste. Taste is supported by the discovery of fatty acid receptors in the tongue papillae. Dietary fat is mainly composed of esterified fatty acids, whereas only free fatty acids can bind to taste receptors. Some authors have mentioned the necessity and efficiency of salivary lipolytic activity to hydrolyse the esterified fatty acids present in foods and enable fat perception. Our hypothesis is that salivary lipolytic activity is also involved in regulating the basal level of salivary fatty acids in humans. To test this hypothesis, total fatty acid (TFA) and free fatty acid (FFA) concentrations and selected salivary characteristics (such as lipolytic activity) were analysed in the resting saliva of 54 subjects. The results show differences in the TFA and FFA profiles, with TFA and FFA concentrations of 8.99 and 3.56 µg/mL of saliva, respectively. Interestingly, lipolytic activity had a significant positive correlation with FFA concentration (0.51, p < 0.01). This result highlights a possible physiological role of salivary lipolytic activity in the regulation of the basal FFA concentration. This regulation could be involved in fat taste sensitivity.